Estrategias de comercialización para incrementar las ventas de las cocadas artesanales en el recinto El Alto de la provincia de Esmeraldas - Fierro Espinoza, Walther Andrés (2016)
The current Project is focus in identify the influence of sales strategies in the market of cocadas in the town El Alto of the state Esmeraldas; for that it have been identify the main features of the product according to the needs of the consumers. Likewise the factors that influence in the purchase decision. This was made by a field study, a marketing research. Between the main findings was that the product requires a package that identify and can help stablish a relationship with a brand…….